"'Histories that All of Us Should Know': Asian American Masculinities in Interethnic Perspective" - Šesnić, Jelena (Array, 2007)
US ethnic studies, specfically their Asian American section, have been marked by a sustained interest in the questions of the models of Americanization through adopting dominant masculine roles, usually presumed "white". The reading of two recent novels from the Asian American canon, namely, Gus Lee's _China Boy_ (1991) and Chang-rae Lee's _Native Speaker_ (1995) suggests, however, that we pay attention to the ways some alternative models of homosocial relations (a term borrowed from Eve Kosofsky Sedgwick) work to counteract the idea of dominant white masculinity, and draw the male protagonists in the novels closer to an interethnic model identity building ususally involving an important African American figure. In the process this also signifies the changes and redefinitions in American social formations which have to do with ethnicity, race, immigration and citizenship status in different phases of the post-Civil Rights period.